Pengaruh Pelaksanaan Vipassanā Bhavana terhadap Pengendalian Diri (Samvara) para Sastri di Pasastrian Buddha Kusalamitra Gunungkidul - Titik Handayani; Suharno Suharno (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Kusalamitra Buddhist Pasastrian in Gunungkidul is one of the institutions that organizes non-formal education. Kusalamitra Buddhist Pasastrian is engaged in non-formal education and training that is social and religious in nature. The Kusalamitra Buddhist Pasastrian organizes religious education and training such as Dharma guidance, meditation practice, religious ceremony practice, guidance and training of Buddhist youth. The habituation of behaving based on Buddhist teachings is the main goal of this Pasatrian Education. One of the education and training programs at the Kusalamitra Buddhist Pasastrian is vipassanā bhavana training. Some students are diligent in implementing vipassanā bhavana, but some are not diligent. In addition, there are still some students who do not have good self-control (samvara). The purpose of the study was to determine the effect of the implementation of vipassanā bhavana on the self-control (samvara) of students at the Kusalamitra Buddhist Pasastrian. This study is a quantitative study with a population of 44 students. The results of the study showed that the implementation of vipassanā bhavana had an effect on self-control (samvara), by 55% and the remaining 45% was influenced by other factors.